Bagaimana kontrol kerja memengaruhi pembelajaran informal pada karyawan senior? - Rizka Maulani Putri; Debora Eflina Purba (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
Informal learning is an important learning strategy for senior workers in the workplace to keep up with their career development. Studies previously have shown that job control predicted informal learning, but critics have argued that previous research has overlooked the psychological mechanisms that explained the relationship. This study aims to examine the mediating effect of occupational future time perspective in the relationship between job control and informal learning on older workers by using the Cognitive-Affective Processing System (CAPS) theory to explain the mediation model. Participants were older workers from various private and state-owned enterprises in Indonesia (N = 183). Data were analyzed using Hayes’s PROCESS macro version 3.4.1 on SPSS. The results showed that occupational future time perspective significantly mediated the relationship between job control and informal learning. As a practical implication, this study provides evaluation materials for organizations in planning programs for older workers in order to improve their occupational future time perspective and informal learning.